2017
DOI: 10.1007/s11011-017-0176-0
|View full text |Cite
|
Sign up to set email alerts
|

The effects of vitamin E on brain derived neurotrophic factor, tissues oxidative damage and learning and memory of juvenile hypothyroid rats

Abstract: The effects of vitamin E (Vit E) on brain derived neurotrophic factor (BDNF) and brain tissues oxidative damage as well as on learning and memory impairments in juvenile hypothyroid rats were examined. The rats were grouped as: (1) Control; (2) Propylthiouracil (PTU); (3) PTU-Vit E and (4) Vit E. PTU was added to their drinking water (0.05%) during 6 weeks. Vit E (20 mg/kg) was daily injected (IP). Morris water maze (MWM) and passive avoidance (PA) were carried out. The animals were deeply anesthetized and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 81 publications
2
27
0
Order By: Relevance
“…The current ndings revealed that hypothyroidism during juvenile growth in rats result in cognitive perturbation which was re ected in animal's performance in both MWM and PA tests. In support of the current data, our previous works showed that hypothyroidism was associated with impaired learning and memory of the rats (11,36,45). In the present study, the results of the MWM test declared that the time spent and distance traveled to nd the platform in the hypothyroid rats was higher than the the control group ones which a rms learning impairment due to hypothyroidism.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The current ndings revealed that hypothyroidism during juvenile growth in rats result in cognitive perturbation which was re ected in animal's performance in both MWM and PA tests. In support of the current data, our previous works showed that hypothyroidism was associated with impaired learning and memory of the rats (11,36,45). In the present study, the results of the MWM test declared that the time spent and distance traveled to nd the platform in the hypothyroid rats was higher than the the control group ones which a rms learning impairment due to hypothyroidism.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, it seems that AChE activity is under direct thyroid hormone control. Nowadays, antioxidants have been generally demonstrated to have bene cial effects in the prevention of memory impairment by neutralizing the excess of free radicals to protect against oxidative damage (36,54). The ndings of the present study implied that treatment with Vit D supplementation enhanced learning and memory tasks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Memory impairment caused by various factors such as aging and lipopolysaccharide could all be alleviated by antioxidants such as naringin and vitamin E (Baghcheghi et al., 2018; Khajevand‐Khazaei et al., 2018). For instance, vitamin E could improve post‐traumatic stress disorder, cisplatin, or waterpipe smoking‐induced memory impairment possibly through affecting alterations in oxidative stress biomarkers including superoxide dismutase (SOD), glutathione (GSH), and methane dicarboxylic aldehyde (MDA) (Ahmed et al., 2020; Alzoubi et al., 2019; Hosseinzadeh et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of malondialdehyde (MDA) concentration was done using relevant reagents as it has been previously declared. 30 Determination of total thiol content The total thiol content (SH) was evaluated using appropriate reagents as we have already described. 30…”
Section: Assessment Of Malondialdehyde Concentrationmentioning
confidence: 99%